Jean-Christophe Maillot's Romeo and Juliet, music by Prokofiev Bernice Coppieters (Juliet), Chris Roelandt (Romeo), Paola Cantalupo (Lady Capulet) ... - Les Ballets de Monte-Carlo - Prokofiev, Sergey 1891-1953 (Les Ballets de Monte-Carlo, 2002)
Jean-Christophe Maillot's Romeo and Juliet transports us into the tormented soul of Brother Lawrence: the action is staged as a flashback to the events leading up to the young lovers' tragic demise. Joined by the Monte Carlo Philharmonic Orchestra under the direction of David Garforth, Bernice Coppieters (Juliet) and Chris Roelandt (Romeo) lead the prestigious Ballets de Monte-Carlo in this riveting 2002 interpretation of Prokofiev's masterpiece. When considering Shakespeare's Romeo and Juliet, the shadowy figure of Brother Lawrence can easily remain in the background. Yet this unassuming friar plays an essential role in the mechanics of the unhappy tale: his well-intentioned interference ultimately leads to the deaths of the two love-struck teenagers. It is this aspect that Maillot brings to the fore in his 2002 Romeo and Juliet, with the curtain rising on Brother Lawrence starkly isolated amidst Ernest Pignon-Ernest's white minimalist scenery, screaming into the void along with the opening chords of Prokofiev's angular score ...
Keywords: Ballets; Webcast; Filmed performances; Internet videos; Feature films; Filmed ballets; Ballets filmés; Spectacles filmés; Vidéos sur Internet